2015
DOI: 10.1021/acs.jproteome.5b00909
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics-Based Analysis of Banana and Pear Ingestion on Exercise Performance and Recovery

Abstract: Bananas and pears vary in sugar and phenolic profiles, and metabolomics was utilized to measure their influence on exercise performance and recovery. Male athletes (N = 20) cycled for 75 km while consuming water (WATER), bananas (BAN), or pears (PEAR) (0.6 g carbohydrate/kg each hour) in randomized order. UPLC-MS/MS and the library of purified standards maintained by Metabolon (Durham, NC) were used to analyze metabolite shifts in pre- and postexercise (0-h, 1.5-h, 21-h) blood samples. Performance times were 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
93
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(107 citation statements)
references
References 41 publications
11
93
1
2
Order By: Relevance
“…We have previously shown that carbohydrate compared to water ingestion during 75 km cycling trials results in muted post-exercise inflammation, and this study would have been strengthened had the research design included a water-only condition. Nonetheless, contrary to our hypothesis, WM ingestion did not add to the well-known anti-inflammatory effects associated with carbohydrate ingestion during exercise [13,40]. …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that carbohydrate compared to water ingestion during 75 km cycling trials results in muted post-exercise inflammation, and this study would have been strengthened had the research design included a water-only condition. Nonetheless, contrary to our hypothesis, WM ingestion did not add to the well-known anti-inflammatory effects associated with carbohydrate ingestion during exercise [13,40]. …”
Section: Discussioncontrasting
confidence: 99%
“…Despite significantly higher plasma antioxidant capacity, l -arginine, nitrate, and citrulline, WM ingestion was not associated with alterations in the pattern of change in inflammation and immune measures. Performance times were comparable between WM and CHO beverage ingestion, supporting previous findings in our lab that high-fructose fruit ingestion supports intensive, long duration exercise to the same degree as sports beverages [12,13]. …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The acute effect of banana intake compared to 6% carbohydrate drink during and after 75-km cycling performance and post exercise resulted in no detectable differences in performance, blood glucose levels, oxidative stress, inflammation and innate immune levels (146). However, further studies compared the effect of the ingestion of banana, water and pear before and during 75-km cycling indicated that banana and pear intake was associated with a meaningful performance enhancement, diminished inflammation, decreased fatty acid mobilization and oxidation and contributes unique phenolics that elevate antioxidant capacity (147).…”
Section: 4-sports Nutritionmentioning
confidence: 97%